Suicidal ideation following internet-delivered tailored CBT for depression – a secondary analysis of a factorial design trial - Käll, Anton; Andersson, Gerhard (Frontiers in Psychiatry, 2024)
Introduction: Suicidal ideation is common in major depressive disorder (MDD) and a risk factor for suicidal behavior. Although it can be reduced with psychological treatments, the risks often make clinicians hesitant to offer treatment. This concerns remote treatment options, such as internet-delivered cognitive behavior therapy (ICBT), which may be considered unsafe. Although previous studies indicate that ICBT can reduce self-reported suicidal ideation both as primary and indirect treatment target, questions remain about under what circumstances ICBT can be offered as the primary treatment. In this secondary report, we investigated the importance of different treatment factors in reducing suicidal ideation via ICBT, including different kinds of therapist support. Methods: We analyzed data from 197 participants from a factorial trial of ICBT for symptoms of MDD. Before inclusion all participants completed a structured clinical interview where obvious suicidal intent lead to exclusion. Suicidal ideation was assessed at pre- and posttreatment using one item of the PHQ-9 and one from BDI-II. The data were analyzed using generalized linear models. Results: The pre- to posttreatment comparisons showed decreases in the reporting of suicidal ideation. Findings were consistent across the two measures that was used. There was no effect of support format and content tailoring. Conclusions: The findings suggest that ICBT can help alleviate suicidal ideation even when it is not the focus of the treatment. This was the case regardless of mode of therapist support, who tailored the treatment content, and if case supervision was available or not.